Melioidosis: a case series from coastal Karnataka, India - Shenoy, Shabari M.; Vaidya, Ankith; Subramanya, Chethan (International Journal of Research in Medical Sciences, 2019)
Melioidosis is an infectious disease caused by gram negative bacteria B. pseudomallei. The disease is largely under diagnosed globally. Sporadic cases have been reported from India, distributed mostly in the coastal areas. Authors present a series of seven culture proven cases of Melioidosis treated at a tertiary care Hospital in the coastal city of Mangalore in South India.